Biochemical and physiological responses of Nile tilapia (Oreochromis niloticus Linn.) subjected to rapid increases of water temperature - Paiboon Panase (2019)
© 2018, Springer-Verlag London Ltd., part of Springer Nature. This research evaluated the general stress response, serum biochemistry, hematology, cortisol level, and ventilation rates of the commercial fresh water fish Oreochromis nilotichus, which was subjected to acute heat shock treatment. The consequences of heat shock were evaluated using five different water temperature levels (25 °C used as the control group, then 27 °C, 29 °C, 33 °C, and 37 °C, the rate was increased 3 °C per hour). All serum indices showed significant changes (p < 0.05), especially with regard to the activities of alanine transaminase (ALT), aspartate transaminase (AST), creatinine, and blood urea nitrogen (BUN), which clearly fluctuated as a consequence of heat shock, from 25 to 37 °C; meanwhile, serum protein and cholesterol levels increased from 25 to 37 °C. The hematological indices, white blood cell count (WBC) was increased but the total red blood cell count (RBC) and mean corpuscular hemoglobin level (MCH) decreased when the fish were exposed to higher temperatures. The cortisol level significantly increased when the temperature rose to 29 °C, and after that, it slightly decreased at 37 °C. Ventilation rates (operculum movement) dramatically increased as the temperature increased. Overall, these results suggested that rapid increases in water temperature may induce stress responses in O. nilotichus, particulary at 29 °C, a temperature that has the potential to impair the physiology and ventilation rate of this species.